Case Report: Maintenance of Desensitization to Nebulized Colomycin Over 10 Years - Sieber, Justyna; Renner, Sabine; Lakatos-Krepcik, Andrea; Szépfalusi, Zsolt (Frontiers in Pediatrics, 2021)
Drug desensitization can be achieved successfully by gradual drug dose increases in different protocols. Most protocols are designed to obtain temporal tolerance. The data on long-term maintenance of drug tolerance is scarce. Based on an IgE-mediated colomycin allergy we describe the successful desensitization of a 15-year-old cystic fibrosis patient by rush intravenous colomycin application over 4 hours, followed by 14-days intravenous treatment and finally a switch to a 10 year lasting colomycin inhalation treatment. The mechanism of drug tolerance is largely speculative; however long-term maintenance of it seems achievable by continuous local drug application.